Case report: Is severe toxicity the price to pay for high sensitivity to checkpoint inhibitors immunotherapy in desmoplastic melanoma? - Squicciarini, Teresa; Villani, Rossella; Apollonio, Benedetta; Fucci, Livia; Zambetti, Milena; Rossini, Michele; Pinto, Rosamaria; Tommasi, Stefania; De Roma, Ileana; Strippoli, Sabino; Guida, Michele (Frontiers in Immunology, 2024)
Background: Desmoplastic melanoma (DM) is a rare subtype of melanoma characterized by high immunogenicity which makes it particularly suitable for immune checkpoint inhibitors (ICIs) treatment. Case presentation: We report the case of a 53-year-old man with metastatic DM successfully treated with the combination of anti-CTLA-4 and anti-PD-1 antibodies, who developed serious immune-related adverse events (irAEs). The primary tumor was characterized by absent PD-L1 expression and no-brisk lymphocytes infiltration. NGS showed absence of BRAF mutation and a high tumor mutational burden and an UV-induced DNA damage signature. Metastatic lesions regressed rapidly after few cycles of ICIs until complete response, however the patient developed serious irAEs including hypothyroidism, adrenal deficiency, and acute interstitial nephritis which led to the definitive suspension of treatment. Currently, the patient has normal renal functionality and no disease relapse after 26 months from starting immunotherapy and after 9 months from its definitive suspension. Conclusion: Efficacy and toxicity are two sides of the same coin of high sensitivity to ICIs in DM. For this reason, these patients should be closely monitored during ICIs therapy to promptly identify serious side effects and to correctly manage.